KETERAMPILAN SOSIAL SISWA DALAM PEMBELAJARAN FISIKA MELALUI PENERAPAN MODEL KOOPERATIF PENDEKATAN NHT DAN TSOS DI KELAS X SMA NEGERI 12 PEKANBARU - Muhammad Nor; Lili Suryani; Zulhelmi Zulhelmi (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2009)
This research aim to know students’ social skill development in learning physic by applyingcopperative model with NHT approach and TSOS to kinematic of rectilinear motion subject in SMANegeri 12 Pekanbaru. This subject of this research is class X4 and the total of the students are 36.The research instrument is observation sheet of social skill. The data collection technique isobservation. The data analyzed descriptively which included 5 indicators: doing task (91,67%)high categories, support participation (75%) high categories, took the turn and share the task(76,56%) high categories, listening actively (86,72%) high categories and asking question(59,38%) medium categories. So that, the application of cooperative model with NHT approachand TSOS could exercised the students social skill at SMA Negeri 12 Pekanbaru to kinematic ofrectilinear motion.